Strengthening Religious Moderation Through Learning National Insight in Early Childhood - Fatimah, Siti; Suryani, Lilis (Journal of Early Childhood Education (JECE), 2024)
Strengthening religious moderation at the Early Childhood Education (PAUD) level is a necessity, because they are in a period of development and growth as a foundation for later life. This research aims to explore the learning of national insight at RA Muslimat NU 007 Gandu I in order to strengthen religious moderation. This type of research is qualitative. The research method used is descriptive analysis. Data collection was carried out by observation, interviews and documentation. Data were analyzed using the Miles & Huberman model, namely data reduction, data presentation and conclusions. The results of the research show, first: learning national insight can strengthen religious moderation, this is shown by children being able to understand the concept of love for the country, the concept of nation and state, the concept of Pancasila as the ideology of the nation and state, as well as the concept of being willing to sacrifice and defend the country. Second: The strategy used consists of two parts, namely through learning materials, especially on the theme of Love for the Motherland and through school programs, both intracurricular and extracurricular.